Quantifying particulate organic matter: source composition and fluxes at the river-estuary interface - Ferchiche, Florian; Liénart, Camilla; Charlier, Karine; Coynel, Alexandra; Gorse-Labadie, Laureline; Savoye, Nicolas (Frontiers in Freshwater Science, 2024)
Particulate organic matter (POM) characteristics and variability have been widely studied along the land-ocean aquatic continuum, yet, gaps remain in quantifying its source composition, fluxes, and dynamics at the river-estuary interface. POM in rivers consists of a complex mixture of sources, derived both from locally produced (i.e. phytoplankton) and from adjacent ecosystems (e.g. terrestrial POM). Each source differ in its trophic and biogeochemical characteristics, hence impacting its integration into local food webs, its transfer to estuaries and sea, and its contribution to biogeochemical processes. In this study, we use a robust approach based on in situ POM to characterize river POM end-members, to quantify POM composition and dynamics, and to identify the related key drivers. This study was performed at the River-Estuary interface of one of the main rivers in Western Europe (the Loire River, France). For 3 years, we conducted bimonthly measurements of carbon and nitrogen isotopic (δ13C, δ15N) and elemental (C/N) ratios to quantify the contribution of two sources (phytoplankton and terrestrial POM) to the POM mixture and calculated annual fluxes of particulate organic carbon (POC) and nitrogen (PN) sources. Throughout the year, POM consisted of 65% phytoplankton and 35% terrestrial POM. The mean annual export fluxes were 40.6 tPOC/year and 2.45 tPN/year over the studied period, with half of it originating from phytoplankton (53 and 55% for POC and PN, respectively). We observed a clear seasonal pattern in POM composition: phytoplankton predominated from March to October, in relation to high primary production, while terrestrial contributions were the highest from November to February, driven by greater autumn-winter hydrodynamics. Our study illustrate the interest of such an approach to quantify POM composition in aquatic system and estimate source fluxes, and provide fundamental results for estimating seasonal baselines in food webs, establishing biogeochemical budgets, and quantifying POM exports to estuarine and marine environments. Applying this methodology across a broad spectrum of aquatic systems should enhance our understanding of biogeochemical processes and organic matter transformation along the land-ocean continuum and illustrates the contribution of these ecosystems to global biogeochemical cycles.